A reforma da educação profissional dos anos 1990 e sua aplicação no currículo do centro federal de educação tecnológica do Rio Grande do Norte - Lima, Ana Paula Marinho de (Universidade Federal Rural do Semi-Árido, 2020)
In this dissertation, we discuss the impacts of the Reform of Professional Education in the 1990s, at the Federal Center for Technological Education of Rio Grande do Norte (CEFET/RN). We seek to answer the following question: how was the Professional Education Reform of the 1990s applied in the curriculum of the CEFET/RN? Therefore, the general objective was to analyze the implications of Reform of Professional Education in the 1990s in the curricular proposal of CEFET-RN. The used methodology was the bibliographical and documentary research. In the bibliographic research, we consulted authors such as: Frigotto (2006), Frigotto and Ciavatta (2003, 2012), Oliveira (2003), Saviani (2011), Ramos (2007), Bresser-Pereira (1997, 1996), Cunha (2005), Shiroma, Moraes and Evangelista (2011), Harvey (2008), Mèszáros (2008) e Harvey (2008). In the documentary research, we carried out an examination of the legislation created by the Ministry of Education during the period of the Professional Education Reform, namely: Decree No. 2,208/1997, Ordinance No. 646/1997, Ordinance No. 1005/1997, Opinion CNE/CEB No. 16/1999 and the Resolution CNE/CEB No. 04/1999. We also analyzed documents elaborated by CEFET-RN: the ETFRN Curricular Proposal (1995) and the Curricular Restructuring Project of the Federal Center for Technological Education of Rio Grande do Norte - volumes I and II (1999). The research is a qualitative one and had as a criterion of analysis the cultural, social and political context in which the documents were prepared, as well as the used theoretical basis. The results showed that before the Reformation CEFET/RN already had a Curriculum Proposal in action, which included in its content the articulation between general and technical disciplines. The training for the subjects was based on the historical-critical conception and on the omnilaterality. With the implementation of the Reform, the institution had to adapt the curriculum to the provisions of Decree No. 2,208 / 1997 and of the Professional Education Expansion Program (PROEP). In this way, CEFET/RN started offering modular and flexible courses. The pedagogical conception, in turn, started to privilege the pedagogy of competences
Keywords: Reforma da educação profissional; Decreto n° 2.208/1997; PROEP; Currículo; CEFET/RN; Reform of professional education; Decree No. 2,208 / 1997; PROEP; Curriculum; CEFET/RN; MULTIDISCIPLINAR::ENSINO